2016
DOI: 10.1093/ntr/ntw114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of State-Level Tobacco Environment on Cigarette Smoking are Stronger Among Those With Individual-Level Risk Factors

Abstract: Introduction: To better understand the impact of the state-level tobacco environment (eg, tobacco control policies, attitudes towards smoking) on cigarette smoking, we examined whether the relationship of state tobacco environments to smoking is modified by individual-level vulnerability factors. Methods:In a nationally representative sample of US adults (N = 34 638), past-year smoking and heavy smoking were examined. State-level tobacco environment was defined by tobacco-related control policies and attitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
(84 reference statements)
0
4
1
Order By: Relevance
“…Existing studies have shown that being in a high smoking prevalence environment is associated with an increased likelihood of smoking. [46][47][48][49] In our study, the data showed that a lower rate in the MRP was not a protective factor for men's smoking, compared with women; although this clearly suggests that moving to a low smoking prevalence environment would not reduce smoking in men, the reasons still need to be explored. Qualitative research from China found that men's smoking was considered 'normal' 50 or acceptable, which might mean that men who smoke are not as sensitive to environmental changes.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Existing studies have shown that being in a high smoking prevalence environment is associated with an increased likelihood of smoking. [46][47][48][49] In our study, the data showed that a lower rate in the MRP was not a protective factor for men's smoking, compared with women; although this clearly suggests that moving to a low smoking prevalence environment would not reduce smoking in men, the reasons still need to be explored. Qualitative research from China found that men's smoking was considered 'normal' 50 or acceptable, which might mean that men who smoke are not as sensitive to environmental changes.…”
Section: Discussioncontrasting
confidence: 55%
“…As for our hypothesis 1, the gap in smoking prevalence and women’s empowerment between the MRP and MSP for women were positively correlated with smoking risk; this indicates that environmental changes were significantly correlated with women’s smoking. Existing studies have shown that being in a high smoking prevalence environment is associated with an increased likelihood of smoking 46–49. In our study, the data showed that a lower rate in the MRP was not a protective factor for men’s smoking, compared with women; although this clearly suggests that moving to a low smoking prevalence environment would not reduce smoking in men, the reasons still need to be explored.…”
Section: Discussionmentioning
confidence: 47%
“…The early age of initiation of tobacco consumption and higher tobacco dependence may also be responsible for high failure rate and dropout in the TCC group than the workplace group in addition to various individual predictors such as sociodemographic variables (socioeconomic status and residence), number of quit attempts, motivational variables, and nicotine-related variables. [3233] Tobacco cessation barriers include poor knowledge, lack of advice and support, lack of motivation, as well as intrapersonal, social, cultural, and financial factors. [34] Most of these barriers may be reduced or eliminated by multiple interventions carried out in our study such as pre-awareness session, focus group discussion, one-on-one counseling, and pharmacotherapy resulting in low dropout rate and adherence to the tobacco cessation program.…”
Section: Discussionmentioning
confidence: 99%
“…There are considerably fewer works devoted to the research of territorial smoking predictors at the international level (28)(29)(30). Moreover, studies of "smoking geography" covering territorial entities between countries and small areas, that is, large regions, provinces, and states within a country, are even more sporadic (31)(32)(33). Apparently, such studies are likely to be of interest mostly for countries with a large territory.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, associations of a specific territorial characteristic with health indicators may not indicate a cause-and-effect relationship, but a relationship mediated by other territorial characteristics. Thus, many researchers of “smoking geography” apply composite socio-economic indices calculated based on several social and economic territorial characteristics at once ( 14 , 15 , 24 , 25 , 28 , 32 ). These studies allow to evaluate socio-economic territorial predictors of health status.…”
Section: Introductionmentioning
confidence: 99%